(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The research aims to identify the requirements for achieving the competitiveness of the local agricultural product of vegetables in the province of Baghdad, and for the purpose of achieving the goal, five areas have been identified to identify the requirements for achieving the competitiveness of the local product of vegetables in the province of Baghdad and included (training extension service providers, extension activities provided to vegetable growers, and technical requirements to achieve the quality of the local agricultural product of vegetables, government legislation and laws, and gain consumer satisfaction), and with reference to previous studies and the subject of research, a questionnaire was used to collect this data. A random sample of employees working in agricultural extension was taken in the Department of Agricultural Extension and Training and its center, and the Department of Agriculture of Baghdad, Karkh and Rusafa and its agricultural departments, numbering (114) employees. The results showed that there is agreement on the importance of the requirements that have been studied as requirements of great importance to the respondents for develop their capabilities, where the requirements of gaining consumer satisfaction came in first place according to the degree of importance to the respondents with a weighted average (3.782) degree. While the requirements of government legislation and laws came in last place according to the degree of importance for the respondents, as they were with a weighted average of (3.692) degrees. The researcher recommended the need to take into account these requirements by the relevant agricultural departments, especially the Department of Agricultural Extension and Training, by subjecting its employees working in agricultural extension to intensive training programs to enable them to carry out their duties in how to guide and educate vegetable farmers with specifications and standards to enhance the competitiveness of the local product and the preparation of extension activities provided to vegetable growers that enhance the quality of the agricultural product and the application of government legislation and laws and their application of the requirements of gaining consumer satisfaction.